2020
DOI: 10.36941/jesr-2020-0129
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Instagram-Assisted Project Based Learning Model on Critical Thinking Skills

Abstract: In today’s 21st century, people are demanded to have the ability to communicate and to think critically. In addition, we are also expected to possess leadership qualities. In achieving such competencies, IT-Assisted Project Based Learning (PjBL) model can be used as an alternative. Hence, this study was conducted, aiming at determining whether there is an effect of Instagram-Assisted PjBL model on students' critical thinking skills in sociology subjects. This research was a Quasi-Experimental Study, with Nonra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…So, based on the description of the calculation and analysis results above, it can be concluded that the YouTube-assisted PjBL learning model influences students' critical thinking skills and self-confidence in physics learning with an average experimental class score higher than the control class. This study's findings align with research (Adekantari et al, 2020;Sularmi et al, 2018), which reveals that the Project Based Learning Model can improve critical thinking skills. Through PjBL, students can come up with their ideas through project activities.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…So, based on the description of the calculation and analysis results above, it can be concluded that the YouTube-assisted PjBL learning model influences students' critical thinking skills and self-confidence in physics learning with an average experimental class score higher than the control class. This study's findings align with research (Adekantari et al, 2020;Sularmi et al, 2018), which reveals that the Project Based Learning Model can improve critical thinking skills. Through PjBL, students can come up with their ideas through project activities.…”
Section: Resultssupporting
confidence: 84%
“…Research on implementing the project-based learning model has been widely carried out. Among them are to improve creative skills (Ningsih et al, 2020), communication skills (Ambarwati et al, 2015;Saimon et al, 2023), critical thinking skills (Adekantari et al, 2020;Sularmi et al, 2018), and higher-order thinking skill (Martawijaya et al, 2023). From the results of previous studies, no researcher has examined two dependent variables at once, critical thinking skills and self-confidence, in the independent variable of the PjBL learning model assisted by YouTube.…”
Section: Introductionmentioning
confidence: 99%
“…In the era of data, the human lifestyle has changed from simple data to big data, AI technology has dived into people's lives, and all aspects have been inseparable from the application of data, changing our production methods, consumption methods, and interaction methods in a big step. This information revolution, marked by the Internet, big data, 5G technology, AI, and other advanced technologies, has brought unimaginable disruptive changes to our lives, is leading human society to a higher civilization, and has had an all-round major impact on technological development and social change, engraving an indelible mark [ 1 ]. The DBiLSTM-SMOTE model achieved an AUC value of 0.726 in stage 3.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, skills and experience in entrepreneurial process are obligatory if one aims to create competitive graduates. Certainly, the key lies in the renewal of entrepreneurial learning in schools and universities through the use of experiential/practice-based learning models as suggested earlier [19][20][21], although the implementation is not yet optimal [6,22]. Practice-oriented entrepreneurial learning can channel the entrepreneurial process, starting from opportunity recognition/identification; opportunity evaluation; opportunity exploitation; new business and established entrepreneurial phase [23].…”
Section: Discussionmentioning
confidence: 99%